Dissecting the Advantages of the Wafa Method in Learning Tahsin Al-Quran - Noer Viatah; Yayuk Fauziyah; Renny Oktafia (International Consortium of Education and Culture Research Studies, 2020)
The Wafa method is the development of the al-Qur'an education system to instill a love for the al-Qur'an to be more comprehensive. The purpose of this study is to analyze the Wafa Method planning in learning the Koran; to analyze the superiority of the Wafa Method in learning the Koran; and to analyze the impact of the Wafa Method on the ability to read and write the Qur'an. In this study using a qualitative approach, this type of research uses a multi-case study design. Data collection techniques by interview, participation observation and documentation. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. To check the validity of the data, it is carried out by means of continuous observation, data triangulation methods, checking the results of peer discussions, transferability, dependability and confirmability. The results of this study indicate that: 1) the design of learning methods using Wafa method is based on the complexity of learning objectives; the value of effectiveness and efficiency and conformity to the conditions and characteristics of students; 2) the application of the Wafa Method uses the strategies and management of students in a variety of classes so that the teaching of the Qur'an is not monotonous; 3) this method has an impact in making it easier for students to memorize the letters and the reading of the Koran each student is good, but there are some things that have a difficulty such as speaking of buzzing, pressure and Jahr letters. The ability to write single hijaiyah letters and continued is good in the correct writing environment.